ZIF-8 nanoparticles coated with macrophage-derived microvesicles for sustained, targeted delivery of dexamethasone to arthritic joints. (6th October 2022) - Wang, Yao; Zhang, Dan; Jia, Ming; Zheng, Xiu; Liu, Yan; Wang, Chenglong; Lei, Fenting; Niu, Hong; Li, Chunhong
Abstract: Dexamethasone sodium phosphate (Dex) is widely used in the clinic for the treatment of rheumatoid arthritis. However, it circulates in the blood for a short time and it is linked to a high risk of severe side effects caused by repeated dosing. Here, we encapsulated Dex onto zeolitic imidazolate framework-8 (ZIF-8) to prepare metal–organic framework nanoparticles with high drug loading efficiency. To prevent clearance by the mononuclear phagocyte system and extend time in circulation, the nanoparticles were also camouflaged with macrophage-derived microvesicles (MV) to obtain the biomimetic drug delivery system MV/Dex/ZIF-8. In vitro and in vivo experiments showed that the nanosystem had high drug loading and encapsulation efficiency, high stability, and long circulation time, and it permitted sustained drug release longer in inflamed joint tissues. Our study provides new insights into designing camouflaged drug carriers to prevent their phagocytosis and prolong their time in circulation.